The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1039/c5cc02049b
|View full text |Cite
|
Sign up to set email alerts
|

Alignment of nanostructured tripeptide gels by directional ultrasonication

Abstract: We demonstrate an in situ ultrasonic approach to influence self-assembly across the supramolecular to micron length scales, showing enhancement of supramolecular interactions, chirality and orientation, which depends on the peptide sequence and solvent environment. This is the first successful demonstration of using oscillating pressure waves to generate anisotropic organo- and hydrogels consisting of oriented tripeptides structures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(37 citation statements)
references
References 39 publications
(1 reference statement)
0
37
0
Order By: Relevance
“…These noncovalent interactions can provide highly organized molecular architectures that display reversible, instant, and visual changes in response to external stimuli, such as ultrasound, shearing stress, light, heating, magnetism, ions, pH, chiral compounds, enzymes, and gases. Typically, supramolecular gels are formed by heating a low‐molecular‐weight (LMW) gelator in an appropriate solvent at a specific concentration, then cooling . The transcription of intrinsic molecular features from the molecular level to complex supramolecular structures is realized in the sol‐to‐gel transition process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These noncovalent interactions can provide highly organized molecular architectures that display reversible, instant, and visual changes in response to external stimuli, such as ultrasound, shearing stress, light, heating, magnetism, ions, pH, chiral compounds, enzymes, and gases. Typically, supramolecular gels are formed by heating a low‐molecular‐weight (LMW) gelator in an appropriate solvent at a specific concentration, then cooling . The transcription of intrinsic molecular features from the molecular level to complex supramolecular structures is realized in the sol‐to‐gel transition process.…”
Section: Introductionmentioning
confidence: 99%
“…Typically,s upramolecular gels are formed by heatingalow-molecular-weight (LMW) gelator in an appropriate solvent at as pecific concentration, then cooling. [26][27][28][29] The transcription of intrinsic molecular features from the molecularl evel to complex supramolecular structures is realized in the sol-to-gel transition process. However,n ot all self-assemblies of LMW molecules result in gelation.…”
Section: Introductionmentioning
confidence: 99%
“…Pappas et al demonstrated that short, curved nanofibres of the tripeptides D FFD and D FFI can be converted to bundles of parallel nanofibres through directional sonication, resulting in strong gels with pronounced supramolecular chirality. 434 342 More strikingly, the azobenzene derivative 43 produces a strong sound-induced LD signal in cyclohexane solutions of its trans form but becomes LD silent when isomerised, due to fragmentation of the fibrous aggregates into non-orientable spheroidal particles (Fig. 46).…”
Section: Gels Under Stressmentioning
confidence: 99%
“…Manipulating system temperature or pH can promote hierarchical order among synthetic nanofibers by balancing intermolecular forces [9][10][11] . Likewise, shear flow, magnetic field, and ultrasound can be applied to induce peptide nanofiber alignment [12][13][14][15] . Alternatively, amino acid sequences can be tailored to promote nanofiber lateral association 16,17 , although these examples have been limited to electrostatic and aromatic-aromatic interactions involving the few natural charged or hydrophobic amino acids, respectively.…”
mentioning
confidence: 99%